A GULSHANI LODGE IN KUMKAPI: MUHSINE HATUN LODGE - Demirdil, Mahmut; Yıldız, Muhammed Ali; Yıldız, Muhammed Ali (Ankara Haci Bayram Veli University, 2023)
Hatun Lodge is one of the first lodges of the Gulshaniyya sect established in Istanbul. The first Gulshaniyya lodges of the city were established in the 16th century under the leadership of Hasan Zarifi Efendi, who was left as the caliph by Ibrahim Gulshani, the founder of the sect. These lodges; Durmuş Dede Lodge in Rumelihisari and Muhsine Hatun Lodge, which was established in Kumkapi and was a masjid converted from a church when it was allocated. Very detailed studies have been carried out about the Durmuş Dede Lodge, where Hasan Zarifi Efendi was the sheikh for many years. However, there is no separate study about Muhsine Hatun Lodge, which started its activities as a Gulshani lodge and which we think has a special value and importance for Gulshaniyya in the city. Considering that women's foundations are an area of interest, there was a need to conduct a study that could present compiled information to researchers, in which Muhsine Hatun Lodge was also discussed. The Istanbul process of Gulshanism has a remarkable background with its developments in the axis of Ibrahim Pasha, Suleiman The Magnificent and Ibrahim Gulshani. It is possible that this situation may have had an impact on this structure to be built in the future. The aim of this study is to try to examine the historical events of Muhsine Hatun Lodge, which is one of the monumental structures of Kumkapi Nişancasi with its 500 year old past, the disasters it affected, its architectural features and its sheikhs. Our study was supported by photographs and compared with the conditions of the building in previous years. The study, which we used document scanning and field investigation techniques, was limited to Muhsine Hatun Lodge in Istanbul of the Gulshaniyya sect. © 2024 Elsevier B.V., All rights reserved.
KUMKAPI'DA BIR GÜLŞENIHANE: MUHSINE HATUN TEKKESI
Keywords: Gulshaniyya; Ibrahim Gulshani; Ibrahim Pasha; Istanbul; Muhsine Hatun; Mysticism